(untitled) (GIST – Education and Learning Research Journal, 2009)
Seeking the best pedagogical practices for bilingual higher education and guided by the principles of the sheltered instruction observation protocol (SIOP), we describe a sub-study of the Sheltered Instruction Research Project (SIRP) which deals with how professors at ÚNICA college in Bogotá, Colombia implement one of the components of the model: building background (BB). This SIOP element involves the connection of prior learning and experiences with the new content material instructors teach. Such connections allow for students to gain better understandings by recalling facts and concepts from previously studied topics. The sources of data used to fulfill the purposes of this 30-day sub-study included class observations, a workshop and a questionnaire. The research explores the usage of direct experiences and childhood memories as the most effective means for uniting a topic with student feelings, age, needs, preferences and realities.